Analysis of herbs-combination of Professor Yang Su-qing in the treatment of psoriasis vulgaris with blood stasis syndrome - Xue Xiao (Editorial Board of Journal of Hainan Medical University, 2021)
Objective: To explore Professor Yang Suqing’s experience in treating blood stasis syndrome of psoriasis vulgaris and analyze the characteristics of its prescription; Methods: Outpatient prescriptions for the treatment of psoriasis vulgaris with blood stasis syndrome were selected and extracted traditional Chinese medicine for standardized processing. Then analyze the data by using set visualization analysis and Apriori algorithm. Results: A total of 149 traditional Chinese herbs were extracted. Among them, and the top 12 commonly used herbs with frequency > 30 were Licorice, Saposhnikovia, Schizonepeta tenuifolia, Angelica sinensis, Paeonia lactiflora, Ligusticum chuanxiong, Rehmannia glutinosa, Cicada slough, Oyster and Keel through the set visualization analysis, herbs association rules analysis, and herbs combination analysis. Saposhnikovia, Liquorice, Schizonepeta tenuifolia, Angelica sinensis and Paeonia Alba are the most commonly used combination of herbs by Professor Yang Suqing in the treatment of blood stasis syndrome of psoriasis vulgaris. Conclusion: In addition to invigorating blood circulation and removing blood stasis herbs, which are preferred for the treatment of blood stasis syndromes, Saposhnikovia and Schizonepeta tenuifolia, etc., are used to synergistically exert the functions of invigorating blood circulation and removing blood stasis and eliminating wind expression, with remarkable efficacy.